Between morality and rationality: an analysis of interpersonal economics in rural Ireland - Salazar, Carles (Economic & Social Studies, 1996)
Social scientists interested in peasant societies have tried to make sense of their economies in terms of the "political" and "moral" economy paradigms. I t is the aim of this paper to assess critically the applicability of such models to the informal sector of Irish family farms and, in so doing, to postulate the necessity of a different theoretical approach. The simplistic dichotomy between "rational" and "moral" behaviour is shown to fall short of a satisfactory account of economic relationships in this particular context. The complex intersection of different forms of rationality on an Irish family farm, half-way between peasant and capitalist agricultural producers, calls for newer and less rigid hypotheses
Keywords: Rural economics; Economic anthropology; Family farming; Ireland